ANALISIS PERBUATAN MELAWAN HUKUM DALAM AKTA PERJANJIAN PENGIKATAN JUAL BELI (PPJB) TANAH ANTARA KOKO PURNOMO SANTOSO DENGAN PT. INTAN PLAZA ADIKA (Studi Kasus: Putusan Mahkamah Agung Nomor 17/K/Pdt/2016) - Haryati Widjaja; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2018)
Contract or agreement is an act pursuant to which one or more individuals commit themselves to one another. Based on the system that chapter III civil code used, chapter III civil code used opened system it means that every people can make an agreement with everybody and about anythings but the contract or agreement must be appropriate with terms of agreement and agreement principles. There are two kinds of agreement, first nominaat agreement, nominaat agreement is an agreement that already have a regulted in law. The second is innominaat agreement, innominaat agreement is an agreement that not regulated in law. condition sale and purchase agreement is innominaat agreement. Condition sale and purchase agreement was appeared because of freedom of contract. Eventhough condition sale and purchase agreement was made because freedom of contract but it must be appropriate with terms of agreement and agreement principles. If the agreement put aside the agreement principles and legal principles, the agreement can be null and void or can be canceled. In Koko Purnomo Santoso’s case, he already been punished for 4 years because, Koko sold lands that belongs to someone else and gave the wrong information in authentic deed. But, Intan Plaza Adika still want to continue the agreement because Intan Plaza Adika is a purchaser with good faith. The district court and high court agree with Intan Plaza Adika. But the supreme court said the opposite with district and high court, the supreme court said the agreement is null and void.